O EFEITO DA APLICAÇÃO DO MICROGEO NA COMPACTAÇÃO DO SOLO - FANAIA, Elianay da Cruz Henrique,; SANTOS, Wesley Vieira,; MARTINS, Jennifer Caroline Vilalba,; NASCIMENTO, Maryanne Ramos,; MENEZES, Roniedison da Silva,; PANACHUKI, Eloi, (ANAIS DO ENIC, 2024)
-